Genotypic Differences in the Effects of Menthol on Nicotine Intake and Preference in Mice - Akinola, Lois S.; Rahman, Yumna; Ondo, Olivia; Gonzales, Jada; Bagdas, Deniz; Jackson, Asti; Davidson-Wert, Nicole; Damaj, M. Imad (Frontiers in Neuroscience, 2022)
Menthol has been shown to exacerbate elements of nicotine addiction in humans and rodents; however, the mechanisms mediating its effects are not fully understood. This study examined the impact of genetic factors in menthol’s effects on oral nicotine consumption by comparing two inbred mouse strains with differing sensitivities to nicotine. C57BL/6J (B6J) mice are nicotine-preferring, while DBA/2J (D2J) mice are not. While the effects of menthol on oral nicotine consumption have been highlighted in B6J mice, it is unknown if they extend to the D2J strain as well. Consequently, adolescent (PND 21) and adult (PND 63), male and female D2J mice were subjected to the nicotine two-bottle choice (2BC) paradigm with orally and systemically administered menthol. Then, we evaluated its impact on nicotine pharmacological responses in conditioned reward and nociception after systemic administration and, lastly, investigated the potential involvement of the TAAR1 gene and α7 nAChRs in menthol’s effects. Menthol failed to enhance oral nicotine consumption in adult and adolescent female and male D2J mice. Moreover, this lack in effect was not due to nicotine concentration, oral aversion to menthol, or basal preference for nicotine. Menthol also failed to augment nicotine reward or enhance nicotine-induced antinociception in D2J mice, demonstrating that genetic background plays a significant role in sensitivity to menthol’s effects on nicotine. Furthermore, TAAR1 or α7 nAChRs did not seem to mediate menthol’s differential effects in D2J mice. These findings support the existence of genotype-specific mechanisms that may contribute to the variable effects of menthol in different populations.